ChemInform Abstract: A Three‐Component Synthesis of Benzochromenodiazocines and Chromenopyridines. Issue 29 (1st July 2013) - Dolatkhah, Zahra; Nasiri‐Aghdam, Mahnaz; Bazgir, Ayoob
Abstract Both heterocyclic frameworks are readily available in the absence of any catalyst.